Internal effective dose assessment for the public based on the environmental radioactivity data in Portugal. (March 2020) - Madruga, M.J.; Gomes, A.R.; Abrantes, J.; Santos, M.; Andrade, E.; Mourato, A.; Libânio, A.; Reis, M.
Abstract: The objective of this work is to estimate the internal effective dose to the Portuguese population due to the radionuclides inhalation (through the air) and the radionuclides intake (through the ingestion of milk, foodstuffs and drinking water) during the year 2017. In the framework of the environmental radioactivity monitoring performed in Portugal, samples of aerosol particles, milk, foodstuffs (individual products and two complete meals, lunch and dinner, corresponding to one-day intake) and drinking water were collected in mainland of Portugal and in Madeira and Azores Islands. After laboratory preparation, the samples were analysed for radionuclides using appropriate radioanalytical techniques. Among the analysed radionuclides, 137 Cs, 90 Sr and 3 H presented very low activity values, and the majority of their activities was below the minimum detectable activities. The natural radionuclides 7 Be and 210 Pb were detected in the aerosol particles and the 222 Rn in drinking water samples. The internal effective dose was calculated considering the radionuclides activity concentrations, the radionuclides conversion factors and either, the Portuguese annual consumption rate for an adult or, the European annual intake rates for three age categories (infant, child and adult). The calculated effective dose, in both cases, corresponds to about 1% of 1 mSv year −1, the limit for public exposure. Therefore, the inhalation and ingestion of the studied radionuclides do not constitute any risk to the health of the Portuguese population and, so, it can be concluded that there is no need to recommend any radiological protection measures. Highlights: Aerosol, milk, foodstuff (individual products, complete meals) and drinking water. Radionuclides were determined using appropriate radioanalytical techniques. 137 Cs, 90 Sr and 3 H presented very low activity values, the majority below the MDA. 7 Be and 210 Pb were detected in the aerosols and 222 Rn in drinking water samples. The internal effective dose represents about 1% of the limit for public exposure.